Sinonasal Solitary Fibrous Tumor: a rare entity - Salvador, Pedro (2021)
Solitary Fibrous Tumors (SFT) are spindle-cell mesenchymal neoplasms mostly described in pleura. Sinonasal SFT are rare, with less than 100 cases reported in literature. We present a case of a 70-year-old female patient with a posterior ethmoidal solitary fibrous tumor occupying the posterior nasal cavity. The patient presented with a 8-month history of unilateral nasal obstruction and epistaxis. Anterior rhinoscopy evidenced a smooth and friable mass, partially obliterating the left choana. CT and MRI revealed a well-circumscribed enhancing mass with no osseous invasion. The tumor was completely removed by endoscopic sinus surgery. Histopathological examination revealed a spindle cell tumor, with a patternless arrangement, within a collagenous stroma, highly vascularized. The tumor cells strongly stained for CD34 and Vimentin, and were negative for epithelial, vascular, neural crest and muscular markers. After 2 years of follow up, the patient remains asymptomatic with no evidence of recurrence.